First Report of Complete Sequence of a blaNDM-13-Harboring Plasmid from an Escherichia coli ST5138 Clinical Isolate - Lv, Jingnan; Qi, Xiuqin; Zhang, Dan; Zheng, Zhou; Chen, Yuehui; Guo, Yinjuan; Wang, Shanshan; Chen, Liang; Kreiswirth, Barry N.; Tang, Yi-Wei; Chen, Zengqiang; Hu, Longhua; et al. (Frontiers in Cellular and Infection Microbiology, 2016)
Since the first report of blaNDM-1, 16 blaNDM variants have been identified among Gram-negative bacteria worldwide. Recently, a novel blaNDM variant, blaNDM-13, was identified in the chromosome of an ST101 Escherichia coli isolate from Nepal. Here we first reported plasmid-mediated blaNDM-13 in a carbapenem-resistant E. coli ST5138 clinical isolate associated with hospital-acquired urinary tract infection from China. blaNDM-13 and blaSHV-12 coexisted on the a ~54 Kb self-transferable plasmid. Compared with NDM-1, NDM-13, NDM-3 and NDM-4 had two amino acid substitutions (D95N and M154L), one amino acid substitution (D95N) and one amino acid substitutions (M154L), respectively. Complete plasmid sequencing showed that blaNDM-13-harboring plasmid (pNDM13-DC33) was highly similar to the blaNDM-1–harboring IncX3 plasmid pNDM-HN380, a common blaNDM-harboring vector circulating in China. In accordance with the structure of pNDM-HN380, pNDM13-DC33 consists of a 33-kb backbone encoding plasmid replication (repB), stability partitioning, and transfer (tra, trb and pil) functions, and a 21-kb antimicrobial resistance region with high GC content between umuD and mpr genes. In conclusion, the present study is the first report of a plasmid-encoded blaNDM-13 and the complete sequence of a blaNDM-13-harboring plasmid (pNDM13-DC33). blaNDM-13 maybe originate from blaNDM-1 located on a pNDM-HN380-like plasmid by sequential mutations.